Labor in the global digital economy : the cybertariat comes of age - Huws, Ursula (New York : Monthly Review Press, 2014)
"For every person who reads this text on the printed page, many more will read it on a computer screen or mobile device. It's a situation that we increasingly take for granted in our digital era, and while it is indicative of the novelty of twenty-first-century capitalism, it is also the key to understanding its driving force: the relentless impulse to commodify our lives in every aspect. Ursula Huws ties together disparate economic, cultural, and political phenomena of the last few decades to form a provocative narrative about the shape of the global capitalist economy at present. She examines the way that advanced information and communications technology has opened up new fields of capital accumulation: in culture and the arts, in the privatization of public services, and in the commodification of human sociality by way of mobile devices and social networking. These trends are in turn accompanied by the dramatic restructuring of work arrangements, opening the way for new contradictions and new forms of labor solidarity and struggle around the planet. Labor in the Global Digital Economy is a forceful critique of our dizzying contemporary moment, one that goes beyond notions of mere connectedness or free-flowing information to illuminate the entrenched mechanisms of exploitation and control at the core of capitalism. "--
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Information technology -- Social aspects; Capitalism -- Social aspects; Work -- Social aspects; Marxian economics; Electronic books